Increased plasma disequilibrium between pro- and anti-oxidants during the early phase resuscitation after cardiac arrest is associated with increased levels of oxidative stress end-products - Muhammad Shoaib; Nancy Kim; Rishabh C. Choudhary; Tai Yin; Koichiro Shinozaki; Lance B. Becker; Junhwan Kim (BMC, 2021)
Abstract Background Cardiac arrest (CA) results in loss of blood circulation to all tissues leading to oxygen and metabolite dysfunction. Return of blood flow and oxygen during resuscitative efforts is the beginning of reperfusion injury and is marked by the generation of reactive oxygen species (ROS) that can directly damage tissues. The plasma serves as a reservoir and transportation medium for oxygen and metabolites critical for survival as well as ROS that are generated. However, the complicated interplay among various ROS species and antioxidant counterparts, particularly after CA, in the plasma have not been evaluated. In this study, we assessed the equilibrium between pro- and anti-oxidants within the plasma to assess the oxidative status of plasma post-CA. Methods In male Sprague-Dawley rats, 10 min asphyxial-CA was induced followed by cardiopulmonary resuscitation (CPR). Plasma was drawn immediately after achieving return of spontaneous circulation (ROSC) and after 2 h post-ROSC. Plasma was isolated and analyzed for prooxidant capacity (Amplex Red and dihydroethidium oxidation, total nitrate and nitrite concentration, xanthine oxidase activity, and iron concentration) and antioxidant capacity (catalase and superoxide dismutase activities, Total Antioxidant Capacity, and Iron Reducing Antioxidant Power Assay). The consequent oxidative products, such as 4-Hydroxyl-2-noneal, malondialdehyde, protein carbonyl, and nitrotyrosine were evaluated to determine the degree of oxidative damage. Results After CA and resuscitation, two trends were observed: (1) plasma prooxidant capacity was lower during ischemia, but rapidly increased post-ROSC as compared to control, and (2) plasma antioxidant capacity was increased during ischemia, but either decreased or did not increase substantially post-ROSC as compared to control. Consequently, oxidation products were increased post-ROSC. Conclusion Our study evaluated the disbalance of pro- and anti-oxidants after CA in the plasma during the early phase after resuscitation. This disequilibrium favors the prooxidants and is associated with increased levels of downstream oxidative stress-induced end-products, which the body's antioxidant capacity is unable to directly mitigate. Here, we suggest that circulating plasma is a major contributor to oxidative stress post-CA and its management requires substantial early intervention for favorable outcomes.